Methodische Fortschritte der wissenschaftlichen Luftbild Interpretation - Schmidt-Kraepelin, Ernst (ERDKUNDE, 1958)
In all branches of studies dealing with the earth’s surface air photographs have been gaining increasing importance. It seems therefore to be an appropriate moment to survey the advances in methods and the scientific results of air photo interpretation as achieved over the last 10—15 years, in particular outside Germany. After a brief review of the most recent developments in technical devices a critical summary is given of the most important rules of interpretations as they apply to all relevant branches of study and also of methodological experiences. This is followed by a section dealing with the application ofairphoto interpretationin thefield of geology. Especially considered are the methods relating to prospecting for oil and ore, techniques of gaining quantitative data and questions of geological mapping. (Contributions dealing with other branches of air photo interpretation are to follow in future issues.)